Mozi : A Study and Translation of the Ethical and Political Writings - Mo, Di, active 400 B.C (Book collections on Project MUSE., 2013)
The authors of the Mozi, an anthology of enormous scope and great importance, can be credited with having produced, during the Warring States period (453{u2013}221 BCE), the earliest extended philosophical discourse in China on a varied set of topics that range from aggressive warfare and prolonged mourning for the dead, to frugality, love for others and belief in divine agency. This study and translation offers a new interpretation of the Mozi's thirty six chapters on political and ethical philosophy. Based on an initial translation by the late John Knoblock, it attempts to understand the Mozi in light of excavated manuscripts and recent scholarship on ancient Chinese philosophy.